2019
DOI: 10.1027/1015-5759/a000443
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Analysis of the Student Version of the Perceptions of Inclusion Questionnaire (PIQ)

Abstract: Abstract. The German version of the Perception of Inclusion Questionnaire (PIQ), which is used to assess students’ emotional inclusion, social inclusion, and academic self-concept, was analyzed with the multi-unidimensional graded response model (GRM) and investigated for differential item functioning (DIF) between students with and without learning difficulties (LD). The PIQ was administered to 823 primary school students in Switzerland ( Mage = 11.94, SD = 1.01 years), of which 190 were classified as having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 23 publications
(26 reference statements)
7
50
4
2
Order By: Relevance
“…English, German, and other language versions of the PIQ are available online to educators and researchers (see Venetz et al, 2015). The scale was further evaluated by Zurbriggen, Venetz, Schwab, and Hessels (2017), where its 3-factor structure was confirmed.…”
Section: The Perceptions Of Inclusion Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…English, German, and other language versions of the PIQ are available online to educators and researchers (see Venetz et al, 2015). The scale was further evaluated by Zurbriggen, Venetz, Schwab, and Hessels (2017), where its 3-factor structure was confirmed.…”
Section: The Perceptions Of Inclusion Questionnairementioning
confidence: 99%
“…However, one item was found to lack measurement invariance between learners with learning disabilities and those without. Zurbriggen et al (2017) concluded that more work is necessary to compare the instrument in general across differing SEN. Furthermore, a comparison of the scale with other established scales will allow for additional cross-validation of its latent variables.…”
Section: The Perceptions Of Inclusion Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…All dimensions are measured via four items rated on a four-point Likert scale (e.g., "I like going to school" for school well-being, "I have very good relationships with my classmates" for social inclusion, and "I do well in my schoolwork" for academic self-concept). High psychometric properties for the student version have been confirmed several times (e.g., Zurbriggen et al, 2017;DeVries et al, 2018;Venetz et al, 2019). The teachers' version of the PIQ (Venetz et al, 2015) was used for teachers' ratings of students' social inclusion, school wellbeing, and their academic self-concept.…”
Section: Instrumentmentioning
confidence: 99%
“…It considers all three subthemes (social inclusion, school well-being, and academic self-concept), takes around 5 min to complete, and is accessible online. 1 Previous studies already demonstrated that it can be used for different subsamples (e.g., students with and without SEN; Zurbriggen et al, 2017 ; DeVries et al, 2018 ; Knickenberg et al, 2019 ). DeVries et al (2018) concluded from the results of their psychometric analysis that the PIQ meets high qualities and therefore is suitable for use in the context of inclusive education.…”
Section: Introductionmentioning
confidence: 99%